2020
DOI: 10.1590/1678-9199-jvatitd-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidant defense in detoxification systems of snake venom-induced toxicity

Abstract: Background: Snakebites remain a major life-threatening event worldwide. It is still difficult to make a positive identification of snake species by clinicians in both Western medicine and Chinese medicine. The main reason for this is a shortage of diagnostic biomarkers and lack of knowledge about pathways of venom-induced toxicity. In traditional Chinese medicine, snakebites are considered to be treated with wind, fire, and wind-fire toxin, but additional studies are required. Methods: Cases of snakebite seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Human envenomation by venomous animals causes changes in plasma protein abundance that are currently monitored by assays that primarily assess changes in hemostasis [ 20 , 21 ]. Additionally, other proteins that are or are not involved in hemostasis have already been identified as potential biomarker candidates but require validation for monitoring clinical complications associated with envenomation [ 67 , 68 , 69 , 70 ]. Furthermore, the possibility of identifying circulating animal toxins in plasma samples from patients after multiple bee stings [ 50 ] and snake bites [ 41 , 71 ] using proteomics tools has already been reported.…”
Section: Biomarkers For Envenomation By Venomous Animals: What To Loo...mentioning
confidence: 99%
“…Human envenomation by venomous animals causes changes in plasma protein abundance that are currently monitored by assays that primarily assess changes in hemostasis [ 20 , 21 ]. Additionally, other proteins that are or are not involved in hemostasis have already been identified as potential biomarker candidates but require validation for monitoring clinical complications associated with envenomation [ 67 , 68 , 69 , 70 ]. Furthermore, the possibility of identifying circulating animal toxins in plasma samples from patients after multiple bee stings [ 50 ] and snake bites [ 41 , 71 ] using proteomics tools has already been reported.…”
Section: Biomarkers For Envenomation By Venomous Animals: What To Loo...mentioning
confidence: 99%
“…Snakebite is a complex neglected health problem, and the greatest treatment consists of the antivenom therapy, mainly preventing or reversing the snakebite effects through the neutralization of their systemic effects and local manifestations. Furthermore, studies also indicate that during envenomation, cellular and plasma oxidative stress increases when patients arrive at the hospital and this increase in cellular and plasma oxidative stress would play an essential role in the pathophysiological process of envenomation [1][2][3]. Moreover, some studies have also shown that polyvalent antivenoms administration induces more oxidative stress and lead to the activation of the complement system C3, C4, and C5.…”
Section: Introductionmentioning
confidence: 99%
“…The AA releasing leads to pro-inflammatory cascade activation, the reactive oxygen species production, and an increased cellular oxidative stress. These events can be evidenced by the presence of several oxidative markers in serum related to lipid peroxidation, which appears to be a crucial event in the induced toxicity of snake venom and can be observed in snakebite patients [6][7][8]3].…”
Section: Introductionmentioning
confidence: 99%
“…Under basal/healthy conditions, the redox metabolism (i.e., the interplay between RS and antioxidant systems) is kept in balance. However, several circumstances might disrupt such balance, leading to redox imbalance and oxidative stress, which ultimately is manifested as excessive oxidative damage to biomolecules, including DNA and proteins . Oxidative stress is associated with chronic kidney, heart, and lung diseases, as well as neurodegenerative diseases, such as Parkinson’s, Alzheimer’s (AD), Huntington’s (HD), and amyotrophic lateral sclerosis .…”
mentioning
confidence: 99%
“…However, several circumstances might disrupt such balance, leading to redox imbalance and oxidative stress, which ultimately is manifested as excessive oxidative damage to biomolecules, including DNA and proteins. 18 Oxidative stress is associated with chronic kidney, 19 heart, 20 and lung 21 diseases, as well as neurodegenerative diseases, such as Parkinson's, Alzheimer's (AD), Huntington's (HD), and amyotrophic lateral sclerosis. 22 The widespread involvement of the disruption of redox signaling and oxidative stress in human pathologies has motivated the development of therapies aimed at the redox metabolism, a field coined redox medicine.…”
mentioning
confidence: 99%